2021
DOI: 10.24251/hicss.2021.357
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Bystander Audience in Online Incivility Encounters: Conceptual Issues and Future Research Questions

Abstract: This paper presents a theoretical exploration of how and why the 1960's bystander theory is a valuable lens through which to study contemporary uncivil online communication, particularly in user commenting spaces. Based on the literature on bystander intervention, which includes extensive field and experimental research on bystander behavior in emergency situations, this paper understands non-target readers of uncivil comments as the bystander audience, which is made up of people who encounter an emerging form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
5
1
Order By: Relevance
“…To our knowledge, this is the first study to comprehensively test all steps and barriers of the BIM in the context of cyber aggression; a noted gap in the literature (Kim, 2021). As the BIM prescribes, our study found a positive, sequential relationship between success in noticing the event (Step 1), interpreting the event as problematic ( Step2), and taking personal responsibility (Step 3).…”
Section: Discussionmentioning
confidence: 60%
“…To our knowledge, this is the first study to comprehensively test all steps and barriers of the BIM in the context of cyber aggression; a noted gap in the literature (Kim, 2021). As the BIM prescribes, our study found a positive, sequential relationship between success in noticing the event (Step 1), interpreting the event as problematic ( Step2), and taking personal responsibility (Step 3).…”
Section: Discussionmentioning
confidence: 60%
“…Bystanders can intervene when they observe a violation of a subreddit's community guidelines, but they can also choose to encourage and reward the behavior. These users fundamentally drive the success of the community through their engagements (Kim, 2021). There has been a growing concern that social media platforms, however inadvertently, are promoting uncivil discussion because the content is engaged with (Davidson et al, 2020).…”
Section: Does Uncivil Content Get Engaged With More?mentioning
confidence: 99%
“…Most social media platforms, including Facebook, provide the opportunity to flag the content of others that potentially violates the commenting policy of the discussion provider. Users can also choose to downvote comments they perceive as inappropriate or intervene against comments of others through counter-speech comments (Kalch & Naab, 2017;Kim, 2021;Naab et al, 2018Naab et al, , 2019. While in traditional media settings users were dependent on institutions to take action against problematic content, social media empower ordinary users to engage against content they perceive as problematic (Lim & Golan, 2011).…”
Section: Actors Intervening In Comment Sectionsmentioning
confidence: 99%